Epitemologi sakral seyyed hossein nasr: kritik atas modernitas dan rekonstruksi ilmu pengetahuan islam - Erlina Uswatun Khasanah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This article examines sacred epistemology (scientia sacra) in the thought of Seyyed Hossein Nasr and its implications for the reconstruction of contemporary Islamic science. Nasr is a key figure in the modern Islamic philosophical tradition, offering a comprehensive critique of modernity, particularly the secularization of science. This article discusses how Nasr's epistemology seeks to integrate revelation, reason, spiritual intuition, and tradition as the foundation of true knowledge. Through a literature review of Nasr's key works, Knowledge and the Sacred, Science and Civilization in Islam, and Islam and the Plight of Modern Man, this article demonstrates that Nasr's critique of modern science is not merely philosophical, but also theological and cosmological. By understanding Nasr's sacred epistemology, this article confirms its relevance in the context of Islamic education, the modern ecological crisis, and efforts to Islamize science. The article concludes that Nasr's ideas provide a coherent and transformative alternative framework for the reorientation of science within the Islamic tradition